The Eighteenth century now - Mallinson, J (Voltaire Foundation, 2017)
Published to mark the fiftieth anniversary of SVEC, this collection of essays examines the current state of eighteenth-century French studies; it revisits a familiar canon, investigates more recently discovered fields of enquiry, and explores new perspectives for research. Eighteenth-century studies today are characterised above all by their re-examination of categories and boundaries. We are witnessing a progressive broadening of the canon, not least in our rediscovery of women's writing, and a reinvestigation of apparently 'minor' works by apparently 'familiar' authors. There has been path-breaking research, too, in areas which reflect our broadening conception of eighteenth-century studies, from literature of travel to post-colonial writing, translation to the press, popular literature to clandestine manuscripts. Different perspectives on eighteenth-century writing have been opened up by new ways of reading which draw on research in cultural studies, history of the book or rhetorical analysis. New insights have emerged from studying the interaction of text and image, word and music, the points of contact between the worlds of science and the arts, of politics, philosophy and literature, exchanges across national and linguistic boundaries, or across the artificial divisions of 'one' century. Inclusive, interdisciplinary and international, this volume embodies the principles which inspired the creation of SVEC by Theodore Besterman in 1955; it investigates our changing images of writers and writing to the categories in which we may try to confine them, from 'Voltaire' to the 'eighteenth century'. The Eighteenth century now suggests our sense of identification with the period, the vibrancy of present research in both individual and collaborative projects, and the promise of immediacy and exchange in the electronic age. But it also evokes the boundaries which remain, financial, institutional, intellectual, and which present the challenge of the future. Its aim is as much to provoke thought as to provide answers, to stimulate as well as to celebrate. List of illustrations Acknowledgements Jonathan Mallinson, The eighteenth century now: reading beyond the lines I. Defamiliarising a canon Nicholas Cronk, Inventing Voltaire Catherine Volpilhac-Auger et Catherine Larrère, Montesquieu en mouvement Marian Hobson, Diderot and oblivion / Diderot in the future tense Jacques Berchtold, Du nouveau dans les études rousseauistes? A propos de l’approche thématique David Coward, Adventures of the novel Simon Davies, Poetry reborn Philip Robinson, Eighteenth-century theatre: the triumph of parody Daniel Brewer, Remembering the Encyclopédie II. Discovering new worlds Marie-Laure Girou Swiderski et Suzan van Dijk, La littérature au féminin Shelly Charles, Traduire au dix-huitième siècle François Moureau, Le voyageur français et les étranges étrangers: bilan d’études sur le siècle des Lumières Anthony Strugnell, Colonialism and its discourses Jean Sgard, L’univers des journaux Lise Andries, Réflexions sur la notion de littérature populaire Antony McKenna, Les manuscrits philosophiques clandestins Mark Ledbury, Imagining the Salon: mapping art criticism in the eighteenth century III. Crossing boundaries Philip Stewart, L’illustration du roman au dix-huitième siècle Michael O’Dea, ‘Visions inintelligibles’ et ‘vérités apocalyptiques’: théorie et pratique de l’opéra français Yannick Séité, Le livre des Lumières et son étude Jean-Paul Sermain, La rhétorique dans l’histoire culturelle, la pensée et les textes littéraires du dix-huitième siècle Anne Vila, Getting cultural: new perspectives in eighteenth-century science studies Catherine Larrère, De la politique des Lumières à celle de la modernité Giuseppi Ricuperati, Définir les Lumières: centres et périphéries du point de vue européen, cosmopolite et italien Michel Delon, Questions de périodisation Summaries Index